Te’o Renda: Its History, Meaning, and Function for the Rotenese Community in the Past and the Present - Philby Tafuakan; Dewi Tika Lestari; Jermias Hartes Van Harling (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2025)
This research aims to examine traditional te'o renda music from an ethnomusicological perspective. Using Ethnomusicology theories by Sri Hastanto that are relevant to those of Mantle Hood, the study explores changes and continuities in the presentation of te'o renda in Rote society. Conducted using qualitative methods, focusing on the discipline of ethnomusicology to understand the meaning and function of traditional music within cultural contexts, the research found that te'o renda and sasandu gong have undergone significant changes. In the past, sasandu and te'o renda played crucial roles in wedding ceremonies, particularly in traditional engagement rituals. However, their current usage has diminished, indicating a decline in their essence and sacredness. Other findings include the history, meanings, and functions of te'o renda for Rote communities past and present, as well as the construction of emic notations applied in te'o renda performances. This approach enables accurate and authentic documentation of traditional music, which is expected to contribute to the preservation and revitalization of Rote music culture. Thus, this research not only enhances theoretical understanding but also provides a foundation for efforts to conserve traditional music through emic notation methods.